2011
DOI: 10.5194/amt-4-1979-2011
|View full text |Cite
|
Sign up to set email alerts
|

ARIS-Campaign: intercomparison of three ground based 22 GHz radiometers for middle atmospheric water vapor at the Zugspitze in winter 2009

Abstract: Abstract. This paper presents the Alpine Radiometer Intercomparison at the Schneefernerhaus (ARIS), which took place in winter 2009 at the high altitude station at the Zugspitze, Germany (47.42 • N, 10.98 • E, 2650 m). This campaign was the first direct intercomparison between three new ground based 22 GHz water vapor radiometers for middle atmospheric profiling with the following instruments participating: MIRA 5 (Karlsruhe Institute of Technology), cWASPAM3 (Max Planck Institute for Solar System Research, Ka… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 49 publications
(51 reference statements)
0
19
0
Order By: Relevance
“…Here, data from 10 January to 31 March 2010 is considered and analyzed to yield daily estimates of water vapor profiles in an altitude range between 10 and 0.02 hPa (approximately 30 to 75 km) with a vertical resolution of approximately 12 km. The uncertainty on MIAWARA-C's profiles is typical for ground based 22-GHz water vapor radiometers as shown in Straub et al (2010Straub et al ( , 2011. The simulated accuracy (determined as the 2-σ systematic error arising from uncertainties in a priori temperature, in calibration and in spectroscopy) is below 16 % at all altitudes, while the simulated precision (determined by propagation of 1-σ measurement noise) degrades from 5 % at altitudes up to 50 km to 18 % between 50 and 75 km.…”
Section: Ground Based Microwave Radiometer Miawara-cmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, data from 10 January to 31 March 2010 is considered and analyzed to yield daily estimates of water vapor profiles in an altitude range between 10 and 0.02 hPa (approximately 30 to 75 km) with a vertical resolution of approximately 12 km. The uncertainty on MIAWARA-C's profiles is typical for ground based 22-GHz water vapor radiometers as shown in Straub et al (2010Straub et al ( , 2011. The simulated accuracy (determined as the 2-σ systematic error arising from uncertainties in a priori temperature, in calibration and in spectroscopy) is below 16 % at all altitudes, while the simulated precision (determined by propagation of 1-σ measurement noise) degrades from 5 % at altitudes up to 50 km to 18 % between 50 and 75 km.…”
Section: Ground Based Microwave Radiometer Miawara-cmentioning
confidence: 99%
“…It can be operated as a standalone instrument as it maintains its own weather station and a calibration scheme that does not rely on other instruments nor the use of liquid nitrogen. Water vapor profiles are retrieved from measured spectra of the pressure broadened 22 GHz rotational emission line (see Straub et al, 2010Straub et al, , 2011 for details on MIAWARA-C). Here, data from 10 January to 31 March 2010 is considered and analyzed to yield daily estimates of water vapor profiles in an altitude range between 10 and 0.02 hPa (approximately 30 to 75 km) with a vertical resolution of approximately 12 km.…”
Section: Ground Based Microwave Radiometer Miawara-cmentioning
confidence: 99%
“…Recent validation efforts (e.g. Haefele et al, 2009;Nedoluha et al, 2011;Straub et al, 2011) have demonstrated the reliability of this technique. Validation studies are an important tool to assess the data quality of an instrument.…”
mentioning
confidence: 99%
“…Moreover, it was shown that changes in middle atmospheric water vapour on time scales longer than the on time scales longer than the duration of a satellite mission can be successfully observed by ground-based instruments [Nedoluha et al, 2009]. Several other ground-based spectrometers have been developed in the last decades to detect the water vapour rotational emission line at 22.235 GHz with detect the water vapour rotational emission line at 22.235 GHz with heterodyne microwave receivers [e.g., Nedoluha et al, 2009;Straub et al, 2011]. Due [e.g., Nedoluha et al, 2009;Straub et al, 2011].…”
Section: Introductionmentioning
confidence: 99%